Magnetic resonance imaging of the pulmonary venous flow pattern in mitral regurgitation. Independence of the investigated vein - Galjee, M A; van Rossum, A C; van Eenige, M J; Visser, F C; Kamp, O; Falke, T H; Visser, C A (European heart journal, 1995)
The aim of the present study was two-fold: first, to quantify characteristic parameters of the pulmonary venous flow pattern in patients with mitral regurgitation by using magnetic resonance phase velocity mapping; second, to determine whether this pattern is dependent on the vein being investigated and the direction of the regurgitant jet. Echocardiographic findings threw doubt on whether the pulmonary venous flow pattern is independent of the vein being investigated and whether the flow velocities in the pulmonary veins have a linear relationship with the volume flow. Flow patterns were assessed in all four pulmonary veins by magnetic resonance velocity mapping in healthy volunteers and in 17 patients with echocardiographically mild and 13 patients with severe regurgitation. No differences were found between the use of velocity or volume flow for characterizing individual curves. The pulmonary venous flow pattern in controls was characterized by six points, a biphasic systolic wave (maximum systolic volume flow: 29 +/- 18 ml.s-1), and end-systolic descent (24 +/- 18 ml.s-1), a biphasic diastolic wave (maximum diastolic volume flow: 69 +/- 22 ml.s-1) and an end-diastolic reversed flow. Reversed end-systolic flow was a characteristic sign of severe regurgitation (-10 +/- 18 ml.s-1). The systolic-to-diastolic flow ratio was lower in severe regurgitation (0.5 +/- 0.6) than in mild regurgitation (1.4 +/- 0.9), P < 0.0001). In severe regurgitation, the normalized time intervals from Q wave to the highest systolic peak and end-systolic descent were of less prolonged duration than in mild regurgitation and controls (P < 0.01). Flow patterns between veins were similar and the median of the correlation coefficients between the curves was the same in patients with or without an eccentric jet, 0.80 and 0.81, respectively. Magnetic resonance velocity mapping is helpful in determining and understanding pulmonary venous flow characteristics. It is demonstrated that the pulmonary venous flow pattern is independent of the vein being investigated irrespective of the regurgitant jet direction, and that it is useful in grading mitral regurgitation.